Rocky Mountain bee plant - Yackel Adams, Amy, photographer (Colorado State University. Libraries, 1997)
Rocky Mountain bee plant (Cleome serrulata) along the road in May 1997.
Keywords: Cleome serrulata; vegetation; SGS